2022
DOI: 10.21203/rs.3.rs-2038922/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Computer, A Choreographer? Aesthetic Responses to Computer-Generated Dance Choreography

Abstract: Is artificial intelligence (AI) changing our culture or creating its own? With advancements in AI and machine learning, artistic creativity is moving to a brave new world of possibility and complexity, while at the same time posing challenging questions, such as what defines something as art, what is the role of human creativity in an automated world, and do we evaluate artificial art in the same way as art made by humans? Across two pre-registered and statistically powered experiments we shed light on the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(27 citation statements)
references
References 12 publications
12
14
1
Order By: Relevance
“…Our results are in line with previous research in the domain of automated journalism and empirical aesthetics that suggest a bias against AI-generated productions-we found a trend for individuals to assign lower values to AI-generated archives compared with original archives, and individuals assigned lower values to archives they themselves categorized as AI-generated [6,[12][13][14]21,26,[45][46][47]. We also support previous findings of a relationship between positive attitudes toward AI and a higher acceptance of AI applications [28][29][30][31]48].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results are in line with previous research in the domain of automated journalism and empirical aesthetics that suggest a bias against AI-generated productions-we found a trend for individuals to assign lower values to AI-generated archives compared with original archives, and individuals assigned lower values to archives they themselves categorized as AI-generated [6,[12][13][14]21,26,[45][46][47]. We also support previous findings of a relationship between positive attitudes toward AI and a higher acceptance of AI applications [28][29][30][31]48].…”
Section: Discussionsupporting
confidence: 91%
“…While the explicit bias was not higher than the implicit bias for archives that were, in reality, artificially generated, we predicted that when participants themselves categorized archives as AI-generated or original, they would continue to show a bias toward AI-generated archives. In line with this, and following on from previous evidence [ 12 , 13 ], we found that participants assigned lower ratings of value to archives they thought were AI-generated compared with those they thought were original. This bias was evident even when choosing to preserve or destroy archives—archives categorized as original were more likely to be preserved, both by participants who did the rating task first and those who did the categorization task first.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations